Hydrolysis Optimization For The Lignocellulostic Waste Treatment With Aspergillus Niger Enzymes - Olivo Urbina, Mylena Alexandra; Díaz Monroy, Byron Leoncio; Haro Barroso, Camilo; Borras Sandoval, Luis Miguel (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The present study aimed to optimize the enzymatic hydrolysis process to degrade cellulose from corn stubble (Zea mays), using enzymes from Aspergillus niger. During the first phase of the experimentation, the content of dry matter, organic matter, ash, crude protein, ethereal extract, lignin and cellulose content of the stubble was determined, using the reference methods of the U. FLORIDA 1970 for its quantification. Subsequently the pre-drying and grinding of the same was carried out, prior to the alkali and acid-alkali pre-treatment processes applied, being dried at 4 different temperatures (45, 50, 55 and 60 ° C). The pretreated residues were subjected to hydrolysis with Aspergillus Niger cellulases (39,125 EU) at different pHs (4.0, 4.8 and 5.6), for 24, 48 and 72 h. at 45, 50, 55 and 60 ° C temperature; quantifying the concentrations of reducing sugars released during digestion. Finally, it was determined that the hydrolysis of the stubble without pretreatment and drying at 60 ° C, at a pH of 4.8 for 72 h., had high concentrations of reducing sugars, becoming an alternative for its use as food or biofuel, after the application of biotechnological processes.